Biaxial shear in RC square beams: Experimental, numerical and analytical program. (1st November 2016) - Tinini, Andrea; Minelli, Fausto; Belletti, Beatrice; Scolari, Matteo
Highlights: Tests on 6 full-scale reinforced concrete beams subjected to inclined shear. Evaluation of the biaxial shear in RC member with and without shear reinforcement. Evaluation of the shear failure envelope for square RC beams. NLFEA for understanding structural response and cracking phenomena of experiments. Extension of ACI Code and Model Code 2010 to biaxial shear. Abstract: There are limited studies about the effect of biaxial shear in reinforced concrete (RC) elements. However, this load condition is quite common in columns subjected to horizontal forces. Moreover, the design and evaluation methods reported in codes do not consider any interaction between the shear strength in the two principal directions of inertia. This paper presents the results of an experimental program on six beams, with square section, subjected to inclined shear, which have been tested in order to understand the influence of the load inclination on the shear failure envelope. Based on the experiments, a new analytical formulation was proposed, with the aim to extend the prescriptions presented in fib-Model Code 2010 and ACI Code to the biaxial shear force. The proposed formulation was finally validated against results from experiments and non-linear finite element analyses (NLFEA).